2004
DOI: 10.1164/rccm.200401-093oc
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Aspergillosis in Critically Ill Patients without Malignancy

Abstract: Using criteria designed for invasive aspergillosis (IA) in patients with cancer, we aimed to determine the impact of IA in patients without malignancy in a medical intensive care unit (ICU). In this retrospective study, 127 patients out of 1,850 admissions (6.9%) hospitalized between 2000 and 2003 had microbiological or histopathologic evidence of Aspergillus during their ICU stay. There were 89 cases (70%) without hematologic malignancy. These patients were classified as proven IA (n = 30), probable IA (n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
374
3
29

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 477 publications
(416 citation statements)
references
References 21 publications
10
374
3
29
Order By: Relevance
“…It has been suggested that late IA diagnosis could lead to poor prognosis. 32 In our study, continuous effort was made by the medical staff to diagnose IA as early as possible. Indeed, serum Aspergillus antigen was tested two times/week during patient aplasia.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that late IA diagnosis could lead to poor prognosis. 32 In our study, continuous effort was made by the medical staff to diagnose IA as early as possible. Indeed, serum Aspergillus antigen was tested two times/week during patient aplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the potential for harmful side-effects due to GC treatment in these patients and the rebound effects that their tapering can cause in the evolution of the inflammatory process are the subject of intense debate [35]. The prolonged use of GCs can alter the phagocytic action of macrophages and alveolar granulocytes, which can facilitate the acquisition of severe bacterial and opportunistic infections [36]. Several studies involving patients with sepsis and ARDS have suggested that high-dose GCs increase the risk of secondary infections [37][38][39]; however, a meta-analysis of moderate-dose GCs for sepsis did not substantiate this observation [40].…”
Section: Role Of Glucocorticosteroids In Severe Pneumoniamentioning
confidence: 99%
“…Özgül olmayan klinik ve radyolojik bulgular ve kolonizasyon-enfeksiyon ayrımının güçlükle yapılabildiği pozitif kültür sonuçları erken tanı konulmasını zorlaştırmaktadır [8][9][10] . İPA için altın standart tanı testi kabul edilen histopatolojik inceleme, YB hastalarının büyük çoğunluğunda yapılamamaktadır 11 . Bu durum, yeni tanı yöntemlerinin kullanıldığı klinik çalışmalara gereksinimi artırmaktadır.…”
Section: Introductionunclassified
“…Nötropenik hastalarda serum GM antijeninin tekrarlayan ölçümleri İPA tanısında kullanılmakla birlikte, ancak nötropenik olmayan hastalarda serum GM ölçümünün duyarlılık ve özgüllüğü düşüktür [12][13][14][15] . Bu olgularda, bronkoalveoler (BAL) sıvısında GM antijeninin saptanmasının İPA tanısındaki duyarlılığı daha yüksektir ve klinik çalışmalardaki önemi giderek artmaktadır 11 .…”
Section: Introductionunclassified